Reliability -based mechanical design - Cruse, Thomas A. (Mechanical engineering (Marcel Dekker, Inc.), 1997)
Discussing the modern tools that support designs based on product reliability, this text focuses on the classical techniques of reliability analysis as well as response surface modelling and physics-based reliability prediction methods. It makes use of the available personal computer tools that permit a host of application examples, and contains an IBM-compatible disk that illustrates immediately applicable software that facilitates reliability modelling in mechanical design.